Pengembangan Wisata Religi Madura Berbasis Maqaṣhid Syariah: Strategi Terpadu untuk Kemajuan Ekonomi dan Spiritual - Holis; Ahmad Musadad; Adiyono; Tri Pujiati (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the integration of maqaṣhid syariah, protection of faith, life, intellect, lineage, and wealth, as the foundational framework for developing religious tourism in Madura. Employing a descriptive qualitative approach, data were gathered via participatory observation, in-depth interviews with religious leaders, site managers, pilgrims, and historical document analysis. Findings reveal persistent challenges in access infrastructure, supporting facilities, guide competencies, and limited digital promotion. The study’s novelty lies in a holistic strategy model grounded in maqaṣhid syariah, encompassing site inventory, physical and digital infrastructure enhancement, community and santri empowerment, branding campaigns, stakeholder synergy, and the establishment of a Halal Industrial Zone. Recommendations highlight the sustained implementation of these six integrated measures to cultivate a safe, comfortable, and competitive religious tourism destination that also strengthens local spiritual values and economic welfare.